Factors Related to the Quality of Life of Patients with Coronary Heart Disease at Saiful Anwar General Hospital, Malang - Imanuna, Mazidah; Eko Wardani, Hartati; Dwi Tama, Tika (KnE Life Sciences, 2021)
Most coronary heart disease (CHD) patients experience a decrease in quality of life that can worsen the prognosis. To the best of our knowledge, no previous study has identified the quality of life of CHD patients in Saiful Anwar General Hospital and its predictors. Hence, this study was conducted to determine the factors related to the quality of life of patients with CHD at Saiful Anwar General Hospital. A cross-sectional study was conducted by selecting 90 patients diagnosed with CHD in 2019 purposively. The instruments used in this study were the DASS-21, SF-36 and social support. Data were analysed using univariate and bivariate with binary logistic regression. The study found that the quality of life of patients with CHD has an average value of 63.29. As many as 88.9% of CHD patients were categorized as having a good quality of life. There was no relationship between the independent variables and the quality of life. Further research needs to be done on potential variables related to the risk factors of the CHD patients’ quality of life, which can subsequently be used as a guideline for optimizing and improving the patients’ quality of life. Keywords: coronary heart disease, risk factors, quality of life